THE INFLUENCE OF STORE ATMOSPHERE, PRODUCT DIVERSITY AND PROMOTION ON CONSUMER PURCHASE DECISIONS AT 212 MART, BATU CITY - Pangestu, Bagas Tri; Aziz, Noor; Fiandari, Yulist Rima (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to examine the effect store atmosphere, product diversity and promotions on consumer purchasing decisions in 212Mart. This data was obtained through a survey using a Google form questionnaire to 100 respondents using the purposive sampling technique on consumers 212 Mart The data analysis technique uses a multiple equation model with the help of SPSS 25. The research findings show that store atmosphere, product variety and promotions influence purchasing decisions positively and significantly while the f test shows that store atmosphere, product variety and promotions influence purchasing decisions simultaneously at 212Mart.